(untitled) (Applied Biological Research, 2015)
The honey is generally heated to prevent crystallization and microbial growth, however thermal treatment may affect honey qualities like antioxidant activity, colour, etc. In this study the kinetics of antioxidant activity change in correlation with honey colour has been studied. Mustard and mixed floral honey samples were heated at 40, 50, 60, 70 and 80°C for 5 to 25 min. and changes in antioxidant activity measured by DPPH method. The results showed that increase in temperature increased kinetic constants so revealing favoured antioxidant activity. The calculated activation energy using Arrhenius equation for antioxidant activity at 40-80°C was 171.65 and 453.36 k calories mol-1 for mustard-based and mixed floral-based honey samples, respectively. Both the samples followed first order kinetics upto 60°C. At 70 and 80°C the kinetic trend for mixed floral sample followed zero order kinetics. The results demonstrated that increase in antioxidant activity was significantly correlated with colour change in honey.